LIVED EXPERIENCES OF FINAL-YEAR NURSING STUDENTS PARTICIPATING IN PEER SUPPORT ACTIVITIES TO REDUCE BURNOUT: A PHENOMENOLOGICAL STUDY - Fir'ad Setya Nugraha; Ahmad Rizqo Abdillah (Universitas Airlangga, 2026)
Introduction: Academic burnout is characterized by emotional exhaustion, depersonalization, and reduced academic efficacy. Final-year nursing students are particularly vulnerable due to academic rigor, clinical expectations, intensive supervision, and the demands of undergraduate thesis completion. During this phase, peer support may function as a relational resource that helps students interpret and manage academic strain. This study aimed to explore and describe the lived experiences of final-year nursing students participating in peer support activities in relation to burnout during the thesis-writing process. Method: A qualitative study with a descriptive phenomenological approach was conducted. Twelve final-year nursing students engaged in thesis preparation were recruited using criterion sampling. Data were collected through face-to-face, semi-structured in-depth interviews and transcribed verbatim. Thematic analysis supported by NVivo 12 was applied, remaining grounded in Husserlian phenomenology through bracketing and reflexive journaling to ensure rigor and trustworthiness. Results: Five themes emerged: (1) contributing factors to burnout, including academic pressures, family constraints, and intrapersonal vulnerabilities; (2) manifestations of peer support in emotional, informational, and instrumental forms; (3) outcomes of peer support reflected in more structured thesis writing, enhanced motivation, and increased self-efficacy; (4) ideal support systems combining peer collaboration and individual coping strategies; and (5) the impact of insufficient peer support, resulting in daily disruption, hindered thesis progress, and psychological distress. Conclusions: Burnout is shaped by academic, relational, and personal factors. Participation in peer support activities strengthens motivation, self-efficacy, and academic engagement, whereas its absence intensifies psychological strain. Supportive peer environments are essential to sustain students’ resilience during thesis completion.